2017
DOI: 10.7554/elife.29236
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley fever phlebovirus NSs protein core domain structure suggests molecular basis for nuclear filaments

Abstract: Rift Valley fever phlebovirus (RVFV) is a clinically and economically important pathogen increasingly likely to cause widespread epidemics. RVFV virulence depends on the interferon antagonist non-structural protein (NSs), which remains poorly characterized. We identified a stable core domain of RVFV NSs (residues 83–248), and solved its crystal structure, a novel all-helical fold organized into highly ordered fibrils. A hallmark of RVFV pathology is NSs filament formation in infected cell nuclei. Recombinant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 60 publications
4
20
2
2
Order By: Relevance
“…We established that NSs alone makes fibrillary aggregates and that these aggregates bind to the amyloid-marker dye ThS, whose interaction with amyloids depends on structures rich in β-sheets. We demonstrated in addition that NSs is strongly resistant to detergents, in line with a recent investigation that was unsuccessful to produce the full-length protein as it forms large aggregates in solution 28 . Our results are also in agreement with structural predictions suggesting that NSs has intrinsically disordered regions and an amino-terminal domain with a high propensity to form β-strands 28,29 .…”
Section: Discussionsupporting
confidence: 85%
“…We established that NSs alone makes fibrillary aggregates and that these aggregates bind to the amyloid-marker dye ThS, whose interaction with amyloids depends on structures rich in β-sheets. We demonstrated in addition that NSs is strongly resistant to detergents, in line with a recent investigation that was unsuccessful to produce the full-length protein as it forms large aggregates in solution 28 . Our results are also in agreement with structural predictions suggesting that NSs has intrinsically disordered regions and an amino-terminal domain with a high propensity to form β-strands 28,29 .…”
Section: Discussionsupporting
confidence: 85%
“…The structure of an RVFV NSs protein was reported, showing a stable core domain that might contain all essential determinants for nuclear translocation and filament formation. While this core domain has only a 15% to 30% sequence identity between phleboviruses, these all have a similar core domain fold, while N‐ and C‐terminal regions are highly variable . In the orthobunyaviruses BUNV and La Crosse virus (LACV), IRF‐3 is suppressed through interfering with the assembly and/or leading to degradation of the host RNA polymerase II complex, which has also been seen in RVFV .…”
Section: Particle Structure and Viral Proteinsmentioning
confidence: 99%
“…It is currently becoming common practice to take the intrinsic disorder predictions into account while designing a protein construct for recombinant expression. The N-or C-terminal disordered tails/domains can be truncated (for example: (14,15)), while long loops connecting neighbouring domains or elements of secondary structure can be shortened to aid conformational stability (16). Unfortunately, the thin line between limiting disorder and affecting the function and correct folding of the protein can easily be crossed and the experimental trial-and-error process often takes long before an improved construct is found.…”
Section: Introductionmentioning
confidence: 99%